(untitled) (Journal of Social Sciences Review, 2022)
Migrant laborer are workers or individuals that migrate within their home countries or to other states for the sake of work. The intention of these employees is not to live permanently in the region or country where they work. Migrant laborer faces many challenges, as well as some benefits. This study analyzed the impact of project assessment, safety management training, and risk assessment on migrant labor. The population of the study is made up of Pakistani food industry workers who have previously worked in various cities and countries. A total of 200 people were contacted, and 180 responses were included in the final analysis. The study is both quantitative and descriptive in nature. Data is collected through a questionnaire and administered on a 5-point Likert scale. Smart PLS is applied to the collected data. The findings demonstrated that project evaluation and risk assessment have a positive impact on migrant labor. Safety management training also has an impact on risk assessment and migrant labor. Moreover, risk assessment mediates the relationship between safety management training and migrant labor in the food industry in Pakistan. The management and policy makers of food industry should focus on project safety measures, and safety management training to protect their migrant labor.